Urban lichens : a field guide for northeastern North America : including New York City, Chicago, Toronto, Boston, New Haven, Philadelphia, Baltimore, Washington, D.C. /: a field guide for northeastern North America : including New York City, Chicago, Toronto, Boston, New Haven, Philadelphia, Baltimore, Washington, D.C. (2021) - Allen, Jessica L; Lendemer, James C
No abstract available